Host–Pathogen Interactions of Marine Gram-Positive Bacteria - Hajarooba Gnanagobal; Javier Santander (Biology, 2022)
Marine Gram-positive bacterial pathogens, including Renibacterium salmoninarum, Mycobacterium marinum, Nocardia seriolae, Lactococcus garvieae, and Streptococcus spp. cause economic losses in marine fish aquaculture worldwide. Comprehensive information on these pathogens and their dynamic interactions with their respective fish–host systems are critical to developing effective prophylactic measures and treatments. While much is known about bacterial virulence and fish immune response, it is necessary to synthesize the knowledge in terms of host–pathogen interactions as a centerpiece to establish a crucial connection between the intricate details of marine Gram-positive pathogens and their fish hosts. Therefore, this review provides a holistic view and discusses the different stages of the host–pathogen interactions of marine Gram-positive pathogens. Gram-positive pathogens can invade fish tissues, evade the fish defenses, proliferate in the host system, and modulate the fish immune response. Marine Gram-positive pathogens have a unique set of virulence factors that facilitate adhesion (e.g., adhesins, hemagglutination activity, sortase, and capsules), invasion (e.g., toxins, hemolysins/cytolysins, the type VII secretion system, and immune-suppressive proteins), evasion (e.g., free radical quenching, actin-based motility, and the inhibition of phagolysosomal fusion), and proliferation and survival (e.g., heme utilization and siderophore-mediated iron acquisition systems) in the fish host. After infection, the fish host initiates specific innate and adaptive immune responses according to the extracellular or intracellular mechanism of infection. Although efforts have continued to be made in understanding the complex interplay at the host–pathogen interface, integrated omics-based investigations targeting host–pathogen–marine environment interactions hold promise for future research.